Proceedings of the 16th International Conference on Cognition and Exploratory Learning in Digital Age (CELDA 2019) 2019
DOI: 10.33965/celda2019_201911l007
|View full text |Cite
|
Sign up to set email alerts
|

Open Distance Learning and Immersive Technologies: A Literature Analysis

Abstract: Open and distance learning (ODL) education provides an opportunity for prospective students who require flexibility in education enabling learning without traditional face to face lecture sessions. Previous literature indicated that there has been a growing curiosity amongst educators, researchers, and pedagogues on employing modern visualization technologies to enrich current educational experiences for students who do not attend face to face lessons. This study aims to explore how new immersive technology ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The present study developed an immersive VR neonatal resuscitation gamification program using Keller's ARCS model (1987), which included neonatal resuscitation nursing knowledge, problem-solving and clinical reasoning ability, self-confidence in practical performance, degree of anxiety, and learning motivation, which have previously demonstrated significant effectiveness ( Jeong and Choi, 2017 ; Nielsen and Harder, 2013 ; Shin et al, 2015 ; Yang, 2021 ). There are conflicting opinions about the possibility of replacing face-to-face simulation training in VR programs using immersive technologies ( Ntaba and Jantjies, 2019 ). Some previous studies ( Brady et al, 2018 ; Liaw et al, 2020 ; Succar et al, 2022 ) have demonstrated that VR programs have serious limitations in replacing face-to-face simulation training.…”
Section: Introductionmentioning
confidence: 99%
“…The present study developed an immersive VR neonatal resuscitation gamification program using Keller's ARCS model (1987), which included neonatal resuscitation nursing knowledge, problem-solving and clinical reasoning ability, self-confidence in practical performance, degree of anxiety, and learning motivation, which have previously demonstrated significant effectiveness ( Jeong and Choi, 2017 ; Nielsen and Harder, 2013 ; Shin et al, 2015 ; Yang, 2021 ). There are conflicting opinions about the possibility of replacing face-to-face simulation training in VR programs using immersive technologies ( Ntaba and Jantjies, 2019 ). Some previous studies ( Brady et al, 2018 ; Liaw et al, 2020 ; Succar et al, 2022 ) have demonstrated that VR programs have serious limitations in replacing face-to-face simulation training.…”
Section: Introductionmentioning
confidence: 99%